Diagnostic accuracy of Fine-Needle Aspiration Cytology (FNAC) in assessing breast swelling: A case series analysis with histopathological correlation - Mohammed Azharuddin; Uzma Alvi; Shazima Sheereen; Abdul Hakeem Attar; Riyazuddin Alvi (Al Ameen Medical College, 2024)
Background: FNAC is a minimally invasive, cheaper, rapid diagnostic technique. For a long time, open surgical biopsy has been considered the most reliable way to diagnose palpable breast lesions. Undoubtedly, core needle biopsy (CNB) and fine needle aspiration cytology (FNAC) have established themselves as the most preferred and highly effective minimally invasive techniques in medical diagnosis. Their high accuracy rate in diagnosing various medical conditions has made them increasingly popular in recent years. These, A triple diagnostic approach that combines clinical examination, mammography, and fine-needle aspiration cytology (FNAC) is the most reliable method for accurately assessing breast lumps. This approach is widely regarded as the gold standard for definitive breast cancer diagnosis. Aim: A prospective study was conducted at the HCG Hospital in Gulbarga to assess the diagnostic accuracy of fine needle aspiration cytology techniques in evaluating breast lesions. Materials and Methods: In this research, we studied 100 cases from July 2022 To August 2023. Results: The FNAC diagnosis was compared with the histological diagnosis. Fibroadenoma was the most common benign lesion, and invasive ductal carcinoma was the most common malignant lesion. Rare lesions were secretory carcinoma, Galactocele, and atypical intraductal papilloma. Conclusion: Breast FNAC is a reliable, simple, and cost-effective first-line diagnostic procedure that is highly accepted by patients and without complications. Due to its simplicity, cost-effectiveness, and good diagnostic accuracy, FNAC is followed as the first-line pre-operative procedure.